Job Loss, Credit Constraints and Consumption Growth - Thomas F. Crossley; Hamish W. Low (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
We use direct evidence on credit constraints to study their importance for household consumption growth and for welfare. We distentangle the direct effect on consumption growth of a currently binding credit constraints from the indirect effect of a potentially binding credit constraint which generates consumption risk. Our data is focused on job losers. We find that less than 5% of job losers experience a binding credit constraint, but for those that do, they experience significant welfare losses, and consumption growth is 24% higher than for the rest of the population. However, even among those who are currently unconstrained and who are able to borrow if needed, consumption responds to transitory income.
Keywords: D12; D91; J64; 330; Job Loss; Credit Constraints; Consumption; Arbeitslosigkeit; Kreditrationierung; Haushaltseinkommen; Konsumentenverhalten; Privater Haushalt; Kanada